KAJIAN TAMPANG LINTANG HAMBURAN ELEKTRON DENGAN ION MELALUI TEORI HAMBURAN BERGANDA (MULTIPLE SCATTERING THEORY) - Nouval Khamdani; Muhammad Nur; Zaenul Muhlisin (Youngster Physics Journal, 2014)
Theoretical studies have been conducted on the Cross-sectional scattering equation which is one of the effects from collisions between electrons with ion. This theoretical studies aim to obtain the differential cross-section scattering equations of electrons with ion. Born approximations were used and convert potential energy into potential energy which is obtained from the distribution of ions in the Debye sphere, so the new equation for the scattering of amplitude that can write  will comparable with total sum of ions and also the scattering of cross section is   will too comparable with the large of Debye sphere. Keywords: scattering of amplitude, scattering of cross section, Born approximation, potential energy, Debye sphere, total sum of ions